Development of a surface tension mediated technique for dry stabilization of mammalian cells - Solocinski, Jason; Osgood, Quinn A.; Rosiek, Eric; Underwood, Lukas; Zikanov, Oleg; Chakraborty, Nilay (PLOS ONE, 2018)
Dry state preservation at ambient temperatures (lyopreservation) is a biomimetic alternative to low temperature stabilization (cryopreservation) of biological materials. Lyopreservation is hypothesized to rely upon the creation of a glassy environment, which is commonly observed in desiccation-tolerant organisms. Non-uniformities in dried samples have been indicated as one of the reasons for instability in storage outcome. The current study presents a simple, fast, and uniform surface tension based technique that can be implemented for lyopreservation of mammalian cells. The technique involves withdrawing cells attached to rigid substrates to be submerged in a solution of lyoprotectant and then withdrawing the samples at a specific rate to an inert environment. This creates a uniform thin film of desiccated lyoprotectant due to sudden change of surface tension. The residual moisture contents at different locations in the desiccated film was quantified using a spatially resolved Raman microspectroscopy technique. Post-desiccation cellular viability and growth are quantified using fluorescent microscopy and dye exclusion assays. Cellular injury following desiccation is evaluated by bioenergetic quantification of metabolic functions using extracellular flux analysis and by a Raman microspectroscopic analysis of change in membrane structure. The technique developed here addresses an important bottleneck of lyoprocessing which requires the fast and uniform desiccation of cellular samples.